Closed-form solution for stress intensity factors of semi elliptical surface cracks with different inclinations in a cylinder bar under pure tension and pure torsion / Mohammadkazem Ramezani - Mohammadkazem, Ramezani (2018)

(untitled)
Surface flaws could occur as internal or external semi-elliptical cracks in cylinder or round bars along the axial or circumferential direction. Fracture analysis has been widely implemented to predict failure of cylinder bars and engineering components caused by preexisting small cracks so that precautionary measures could be taken to either prevent future crack propagation or to determine the remaining life of the components. In order to achieve this, the Stress Intensity Factors (SIFs) must be evaluated accurately for the different Modes of fracture and crack geometries. Many approaches and models have been proposed in the literatures to evaluate the SIFs of cracks based on finite element analysis. However, very little works has focused on using the Dual-Boundary Element Method (DBEM) which is a more reliable and robust tool to evaluate the SIFs for a wide range of cracks. In this research, a systematic study was undertaken to use DBEM-based software BEASY to analyze the SIFs of semi-elliptical surface cracks with different inclination angle in cylinder bar subjected to pure tension and pure torsion. The main parameters being considered in this work to evaluate the SIFs were the crack depth to cylinder diameter ratio (